Energy management implementation in an office building via peak shaving method / Behzad Rismanchi - Behzad, Rismanchi (2013)
In our today’s world, one of the main indicators of a country’s development is its electricity usage per capita. The electricity usage in developed and developing countries are critically being studied by the researcher and the results are being used by the policy makers in order to get the most from every drop of the valuable energy resources. Among all energy consumers, the commercial buildings are known as the second most electricity users around the world, in which the air conditioning (AC) systems have a significant share. Between 16% to 50% of the total electricity demand in the commercial buildings is dedicated to the AC systems, this share increased in tropical conditions of Malaysia up to 57%. In order to control the electricity demand, several methods have been established so far under the load management techniques in which the system is designed in a manner to bring more harmonic between electricity production and demand. In the context of this study, the application of utilizing cold thermal energy storage (CTES) system for building load management technique via peak shaving method is critically analysed through various viewpoints from thermodynamic evaluation to the environmental impact and economic assessment. In the present work, a detailed field survey was conducted on a newly build 10-story office building for a period of 6 months to calculate the average weekly electricity demand pattern. The electricity demand, inside and outside temperature, inside and outside humidity, the light intensity, CO and CO2 concentration levels were recorded continuously with short intervals and high accuracy. The accuracy of the recorded data was analysed and the uncertainty level was calculated. The resulted energy demand pattern was used to evaluate the conventional system performance and to design various system configurations by utilizing CTES application. The thermodynamic assessment shows that the CTES systems are highly efficient in terms of energy efficiency with minimum efficiency of 93% and maximum of 98%. However, the exergetic efficiencies were much lower than the energy efficiency, the maximum exergy efficiency for ice-on-coil system was obtained to be 18%. The economic impact of utilizing CTES systems was also investigated from two different viewpoints of short-term and long-term impacts. The result reveals that the full storage strategy can reduce the annual cost of the AC system up to 35% while this reduction is limited to around 8% for a load levelling strategy. The payback period of the full storage strategy varies between 3 to 6 years while the payback period for the load levelling strategy varies between 1 to 3 years. The energetic analysis reveals a potential for energy saving of up to 3.7% by implementing load levelling storage strategy that would consequently reduce the carbon footprint. Finally yet importantly, the proposed system was simulated via using TRNSYS simulation software in order to predict system behaviour throughout the year. The computer simulation was validated with the recorded data from the building. The validated model was used to calculate the potential energy saving by using CTES system. The results confirmed the approximate 4% energy saving potential of load levelling storage strategy. From this perspective, it can be stated that utilizing CTES system can play a vital role in consuming the natural resources in a more efficient, economic and environmentally benign way by changing the electricity consumption pattern to overcome the disparity between energy generation and energy demand.